DESAIN DAN APLIKASI MARKA GRAFIS BERBASIS KAWASAN PROTOKOL KESEHATAN PENCEGAHAN COVID 19 DI SMA DAARUT TAUHIID BOARDING SCHOOL - Gema Arifrahara; Didit Widyatmoko (Universitas Trisakti, 2023)
Health protocols in order to prevent the spread of covid 19 is part of the government’s program to reduce the spread of the corona virus in community. It has been more than a year since the outbreak of the corona virus in Indonesia, this country has implemented a policy so that people carry out all their activities from home, including teaching and learning activities. Daarut Tauhiid Boarding School has implemented a distance learning policy since 2020 until now. In July 2021, Daarut Tauhiid Boarding School has carried out face-to-face learning which requires some preparation, especially in implementing health protocols in schools. Graphic marking is one of the technical tools supporting the implementation of health protocols. The design of graphic markings supporting health protocols should also pay attention to the area whereit is embedded because it is related to the activities of the user population of the place. This design aims to conceptualize and apply graphic markings of health protocols at Daarut Tauhiid Boarding School which refers to the character of the area. Analysis of existing problems is carried out using qualitative data, based on observations, interviews, and literature searches related to the problems faced by Daarut Tauhiid Boarding School. The results of the analysis are then realized in the form of design implementation and application at Daarut Tauhiid Boarding School. Area-based graphic markings that support the enforcement of health protocols are one of the pioneering tools for maintaining the face-to-face teaching and learning process at Daarut Tauhoid High School.Keywords: graphical markings, region-based, health protocols